Hypoxia-Inducible Factor mediates the Release of Natriuretic Peptides - Arjamaa, Olli (European Society of Medicine, 2025)
Background: The physiology of natriuretic peptides is insufficiently known. The function of mechanical heart alone, mediated by large and rapid volume overloads, has been suggested to be the key operator in the synthesis and release of natriuretic peptides from the endocrine heart. Researchers have concluded that terrestrial mammals, including humans, have a powerful endocrine system that responds to the mechanical stress of the heart by causing instantaneous diuresis and natriuresis. Although one of the most important and valid paradigms in cardiology is that mechanical load increases the oxygen consumption of heart, the investigation of the relationship between mechanical load and oxygen metabolism has been neglected in the studies on circulating natriuretic peptides.
Purpose: To develop a comprehensive conceptual model explaining how the oxygen metabolism plays a central role in the biology of natriuretic peptides.
Conclusions: All cells including cardiac myocytes, share an oxygen sensing pathway which is regulated through a nuclear transcription factor, the Hypoxia-Inducible Factor. When the oxygen concentration is normal Hypoxia-Inducible Factor is rapidly oxidized, whereas in hypoxic conditions, Hypoxia-Inducible Factor starts to accumulate and trigger downhill the expression of hundreds of genes such as the genes for A-type and B-type natriuretic peptide. As a result of diuresis, natriuresis, and plasma shift from intravascular space to extravascular space, circulating natriuretic peptides cause volume contraction and hemoconcentration contributing to the transport of oxygen into tissues and organs.
Implications: Understanding the biology of natriuretic peptides in cardiac diseases would increase the usefulness of plasma measurement of natriuretic peptides.
Keywords: Natriuretic peptide, hypoxia-inducible factor, hypoxia, oxygen